PREDIKSI EROSI PADA BEBERAPA PENGGUNAAN LAHAN DI DESA LABUAN TOPOSO KECAMATAN LABUAN KABUPATEN DONGGALA - Kasmawati, Kasmawati; Hasanah, Uswah; Rahman, Abdul (AGROTEKBIS, 2016)
Erosion is one of the factors that causing the decline in soil capacity to support good agriculture production. This often happened in some land use when the land is managed without pay attention to soil conservation and or the soil capacity to support production. Soil erosion prediction can be good information for local government and soil erosion index of several land use types including non-agriculture can be used to manage sustainability of development. The purpose of this study was to predict the soil erosion rate and determine soil erosion erosion index on several land use types at the Labuan Toposo village Donggala District. The soil was analyzed at soil science laboratory of Tadulako University. The study was conducted from October to January 2016. This study was used the method direct survey in the field and continued with the soil sampling for laboratory analysis. Then the analysis result was further processed by using the equation USLE (Universal Soil Loss Equation ). This study showed that the erosion index that occurredat the village of Labuan Toposo was diverse while the erosion hazard index was lowest for forest land, and the highest was found for teak and coconut. This was caused by land use patterns, land management measures, in addition the high erosion hazard index indicate the potential to cause erosion. It is therefore vital to do conservation measures to prevent erosion e.g. by inter cropping and the use of crop residue on land surface such as mulching.Key Words : Erosion Prediction, Land Use and Village Labuan Toposo.